2003
DOI: 10.1037/1064-1297.11.1.26
|View full text |Cite
|
Sign up to set email alerts
|

The balloon analogue risk task (BART) differentiates smokers and nonsmokers.

Abstract: In trying to better understand why individuals begin and continue to smoke despite the obvious health consequences, researchers have become interested in identifying relevant personality variables, such as risk taking. In this study, the authors compared the ability of 2 behavioral measures of risk taking, the Bechara Gambling Task (BGT) and the Balloon Analogue Risk Task (BART), to differentiate smokers and nonsmokers. Self-report measures of impulsivity and sensation seeking were taken for comparison with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
413
14
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 450 publications
(459 citation statements)
references
References 32 publications
20
413
14
3
Order By: Relevance
“…Nevertheless, smokers generally score relatively highly on such scales (e.g. Lejuez et al, 2003;Mitchell, 1999). Whilst Doran et al (2004) found one widely used measure of trait impulsivity to predict speed of relapse in adult smokers, Krishnan-Sarins et al (2007) found no such relationship in adolescents; interestingly, however, in this group relapse was predicted by two behavioural indices of impulsiveness (delay discounting and commission errors on a Continuous Performance Task).…”
Section: Response Inhibition / Inhibitory Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, smokers generally score relatively highly on such scales (e.g. Lejuez et al, 2003;Mitchell, 1999). Whilst Doran et al (2004) found one widely used measure of trait impulsivity to predict speed of relapse in adult smokers, Krishnan-Sarins et al (2007) found no such relationship in adolescents; interestingly, however, in this group relapse was predicted by two behavioural indices of impulsiveness (delay discounting and commission errors on a Continuous Performance Task).…”
Section: Response Inhibition / Inhibitory Controlmentioning
confidence: 99%
“…Relative to non-smokers, smokers have been found to be impaired on behavioural indices of impulse control in oculomotor (antisaccade), go/no-go, and delayed alternation tasks (e.g. Spinella, 2002), to take more risks in decision-making (Lejuez et al, 2003) and to show abnormally strong preferences for immediate or certain rewards over larger but delayed or less certain rewards (delay or probability discounting; e.g. Bickel et al, 1999;Mitchell, 1999;Reynolds et al, 2004).…”
Section: Response Inhibition / Inhibitory Controlmentioning
confidence: 99%
“…16,34 Specifically, risk-taking on the BART is highly correlated with measures of sensation seeking, impulsivity, and deficiencies in behavioral constraint, as well as with self-reported occurrence of addiction and other risky behaviors. [16][17][18]34 The BART simulates a balloon being inflated by the participant with each click of a mouse. Each pump is worth 5 cents.…”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18] While the protocol allowed for recreational drug use in the past (defined as drug use without diagnosis of abuse, dependence, or participation in a detoxification program), individuals were excluded for recreational drug use within the past week. Smoking was not considered an exclusion criterion.…”
Section: Inclusion/exclusion Criteriamentioning
confidence: 99%
“…Also, riskiness on the BART was correlated with the selfreported occurrence of addictive, health, and safety risk behaviors. Subsequent research with adults has provided further evidence for a correlation between BART scores and substance use in community and clinical samples Lejuez et al, 2003;Pleskac et al, 2008). Following this work, the BART was extended to middle adolescents (ages 14-17).…”
Section: Introductionmentioning
confidence: 99%